Repurchase and condonation of external debt in a voluntary repudiation model - Kenen, Peter B. (Estudios Económicos de El Colegio de México, 1991)
Debt reduction is usually analyzed in models where default is involuntary and the gains from debt reduction derive from various disincentives linked to a large debt overhang. This paper uses a model in which default is voluntary and shows that debt reduction can be beneficial even in absence of those disincentives, by inducing debtors to renounce or postpone repudiation.